Pengaruh Fluktuasi Nilai Tukar Rupiah terhadap Rasio Pertumbuhan Aset Perbankan Syariah - Ahmad Chumaidi Tarmizi Muslikhati (Universitas Muhammadiyah Malang, 2017)
This research aims to reveal empirical evidences about the influence of exchange rate fluctuations to asset growth ratio of sharia banking, along with how much does independent variable explain dependent variable. The research takes a quantitative approachment, which refer to numeral calculating of research data. This research variabel consists of exchange rate fluctuations as independent variable and asset growth ratio of sharia banking as a dependent variable. Sample selection using purposive judgment sampling method. The sample of this research is sharia bankingin the period between 2008-2016. Data used in this research is secondary data while the techniques of data analysis in this research applied simple linear regression analysis. Results of this study demonstrate that the exchange rate fluctuations variable significantly influence to asset growth ratio of sharia banking variable. Regression coefficient value is – 1,73 and significant value is 0,029. The results of this study as well exhibit that the exchange rate fluctuations variable explained 51% of asset growth ratio of sharia bankingvariable while the remaining 49% wereexplained by another variable not included in the model.